MpAMT1;2 from Marchantia polymorpha is a High-Affinity, Plasma Membrane Ammonium Transporter. (12th February 2018) - Guo, Hanqing; Wang, Nu; McDonald, Tami R; Reinders, Anke; Ward, John M
Abstract: Plant ammonium transporters in the AMT/MEP/Rh (ammonium transporter/methylammonium and ammonium permease/Rhesus factor) superfamily have only been previously characterized in flowering plants (angiosperms). Plant AMT1s are electrogenic, while plant AMT2s are electroneutral, and MEP and Rh transporters in other organisms are electroneutral. We analyzed the transport function of MpAMT1;2 from the basal land plant Marchantia polymorpha, a liverwort. MpAMT1;2 was shown to localize to the plasma membrane in Marchantia gametophyte thallus by stable transformation using a C-terminal citrine fusion. MpAMT1;2 expression was studied using quantitative real-time PCR and shown to be higher when plants were N deficient and lower when plants were grown on media containing ammonium, nitrate or the amino acid glutamine. Expression in Xenopus oocytes and analysis by electrophysiology revealed that MpAMT1;2 is an electrogenic ammonium transporter with a very high affinity for ammonium (7 M at pH 5.6 and a membrane potential of –137 mV). A conserved inhibitory phosphorylation site identified in angiosperm AMT1s is also present in all AMT1s in Marchantia . Here we show that a phosphomimetic mutation T475D in MpAMT1;2 completely inhibits ammonium transport activity. The results indicate that MpAMT1;2 may be important for ammonium uptake into cells in the Marchantia thallus.